Pelatihan Pemanfaatan Google Apps for Education di Sekolah Menengah Pertama Muhammadiyah Cisalak - Muhammad Arifin Rahmanto; Bunyamin Bunyamin; Aan Siti Nurjanah (Jurnal Pemberdayaan Masyarakat, 2023)
Learning that takes place at SMP Muhammadiyah Cisalak has implemented learning media in the form of Google but only a few features have been applied. In an effort to optimize the learning process in a more effective classroom, the solution to the problem offered to Partners is to provide training in the use of existing facilities in Google Apps for Education including Google Classroom, Google Form, and Google Drive. These Google facilities are an alternative learning model that is relevant in and current with the Blended Learning model. This training aims to improve the ability of teachers in teaching so that learning will run more effectively and become more professional teachers. This activity was carried out smoothly and well and enthusiastically by participants attended by all Muhammadiyah Cisalak Junior High School teachers and Tendik staff. This training uses a panel discussion method and hands-on practice of utilizing Google Classroom, creating Google Forms, and Google Drive as a storage medium that has a large capacity and is digital-based, and no longer needs to use a flash drive or external hard drive. The output of this activity will be provided with modules and video tutorials on the use of Google Apps for Education. This training activity takes place online through zoom meetings